Characterization of antagonistic rhizobacteria and bio-priming for the control of fusarium proliferatum, causing bakanae disease in rice - Ramli, Nurul Wahida (2015)
Rice is the staple food of Malaysians and mainly planted for domestic consumption. Diseases are estimated to cause annual yield and quality losses of 8 to 10 percent. Production costs are also increased by the use of chemicals and cultural methods of disease control. Bakanae disease is one of the important diseases of rice. Major rice growing areas in Malaysia affected with Bakanae disease showed a significant decrease on yield and quality. Biological control of plant pathogens by antagonistic microorganisms is a potential non-chemical means in managing soil borne plant diseases. Beneficial bacteria and fungi applied as seed treatments provide unique opportunities for protection against soil-borne fungal pathogens and they are potential alternative to fungicides. The objectives of this study are, therefore, to isolate,characterize and identify the antagonistic microorganisms in rice and to evaluate their potential as bio-inoculants against Bakanae disease in rice. From the total of 315 microorganisms isolated from 25 different samples of rhizosphere soil and rice roots,71% were bacteria, 27% fungi and 2% actinomycetes. The isolated microbial organisms were subsequently tested for their antagonistic activity in vitro against Fusarium proliferatum. In dual culture testing, 12 bacterial isolates exhibited significantly high antagonistic activity in the range of 53 to 84%. The highest antagonistic activities were based on their percentage inhibition in radial growth of F.proliferatum (84%), which was exhibited by isolate B7. Secondary screening was carried out for detection of microbial compounds, siderophore production, chitinase activity, indole-acetic acid production and phosphate solubilizing activity for the potential isolates. Isolate B7 was able to produce siderophore, chitinase, and IAA,and had P solubilizing activity. B7 was identified by the Biolog® identification system as Bacillus cereus. Subsequently, molecular characterization also confirmed B7 as Bacillus cereus. Based on their colonization and establishment in rice seedlings, B.cereus (B7) were selected for further in vivo screening for its efficacy in controlling Bakanae disease on rice in the glasshouse. Seed treatment with B. cereus on rice seedlings pre-inoculated with F. proliferatum suppressed the Bakanae incidence compared to the control. Inoculation of seedlings with B. cereus reduced Bakanae incidence by 51%. Based on this disease reduction from this research, B. cereus showed potential to be used as bio-inoculant for controlling Bakanae disease on rice.